Risk of Hospitalization Associated with Cardiovascular Medications in the Elderly Italian Population: A Nationwide Multicenter Study in Emergency Departments - Crescioli, Giada; Bettiol, Alessandra; Bonaiuti, Roberto; Tuccori, Marco; Rossi, Marco; Capuano, Annalisa; Pagani, Silvia; Spada, Giulia; Venegoni, Mauro; Vighi, Giuseppe Danilo; Mannaioni, Guido; Vannacci, Alfredo; et al. (Frontiers in Pharmacology, 2021)
Background: There is a significant gap in knowledge addressing cardiovascular (CV) medications safety in elderly. In this context, the aims of the present study were to describe clinical and pharmacological characteristics of outpatients’ adverse drug events (ADEs) related to CV medications as cause of emergency department (ED) visits in different elderly age groups in Italy, and to estimate the risk of hospitalization associated to ADEs in this population. Methods: A nationwide, multicentre, retrospective study was performed on reports of suspected ADEs collected between 2007-2018 in 94 EDs involved in the MEREAFaPS Study. Elderly patients who experienced one or more CV medications-related ADEs leading to ED visit were selected. Patients’ characteristics, suspected (ATC classes B and C) and concomitant drugs, and ADE description were collected. Elderly patients were stratified into three age groups (65-74, 75-84, and ≥85 years) and compared to adults (18-64 years). Logistic regression analyses were used to estimate the odds ratios (ORs) with 95% confidence intervals (CIs) of ADE-related hospitalization adjusting for sex, presence of two or more suspected drugs, concomitant drugs, and one or more comorbidities. Results: Among elderly, 16,926 reports of suspected ADE related to CV medications were collected, and 6,694 (39,5%) resulted in hospitalisation. Patients were mostly female, Caucasians, and middle-old (75-84). 78.9% of patients were treated with only one suspected drug, and 71.9% and 47.1% reported concomitant medications and comorbidities, respectively. Compared to adults, risk of hospitalisation was significantly higher for middle-old and oldest-old patients exposed to vitamin K antagonists (1.29 [1.09-1.52] and 1.56 [1.30-187]), direct thrombin inhibitors (3.41 [1.44-8.08] and 4.12 [1.67-10.17]), antiplatelets (1.51 [1.26-1.81] and 2.09 [1.71-2.57]), and beta-blockers (1.89 [1.38-2.59 and 2.31 [1.60-3.35]). Overall, a higher risk of hospitalisation was observed for renin-angiotensin system inhibitors (1.32 [1.04-1.68], 1.65 [1.32-2.06], and 2.20 [1.70-2.85]), presence of two or more concomitant drugs, and concomitant conditions. Conclusions: Our real-world findings underline relevant safety aspects of CV medications in the elderly Italian population. ED clinicians must always consider the higher risk of hospitalisation related to the use of CV drugs in elderly, particularly in oldest-old ones, for antiarrhythmics, beta-blocking agents, renin-angiotensin system inhibitors, antiplatelets, and anticoagulants.